POLÍTICA DE IMPLEMENTAÇÃO DE CARGA HORÁRIA NA MODALIDADE EAD EM CURSOS PRESENCIAIS DE GRADUAÇÃO: o caso da UFMS e UFG - Kelly Cristina da Silva Ruas (2023)
The theme of this research deals with the provision of course loads through the Distance Education (EaD) modality in face-to-face undergraduate courses, with a focus on institutional policies. The research proposal is justified by the observation that, in recent years, in Brazil, there has been an expansion in the provision of distance learning, and, as of 2001, there has been, specifically, the legal possibility of offer part of the course load in the distance learning modality in face-to-face undergraduate courses. It is also noted that, from 2001 to 2019, five different ordinances have already been published on the topic, the most recent of which revokes the previous one, establishing a new legal framework for the sector. Given this phenomenon, it is necessary to investigate the trajectory of policies that institutionalize the offering of distance learning courses in face-to-face undergraduate courses. This investigation is linked to the line of research History, Policies, Education of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul and its general objective is to analyze the implementation of the distance learning course load in face-to-face undergraduate courses at universities federal institutions of Mato Grosso do Sul (UFMS) and Goiás (UFG), based on the procedures adopted by these institutions until 2019. The research corresponds to a comparative or multiple case study, and has the UFMS as its locus of investigation. and the UFG. Methodologically, the study has a qualitative approach, developed from the perspective of the research cycle proposed by Minayo (2005). In the field research, it was decided to use two procedures for data collection: documentary analysis, using institutional documents, and application of a questionnaire to the research subjects: coordinators of some face-to-face undergraduate courses at Higher Education Institutions (HEI). researched. The adopted framework relies mainly on the theoretical contributions of Dourado (2001, 2008, 2011, 2020), Dresch, Lacerda and Antunes Júnior (2015), Giolo (2008a, 2008b, 2018), Lima (2013, 2014a, 2014b), Moore and Kearsley (2011, 2013) and Segenreich (2009, 2011, 2013, 2014, 2018). As a result, the research identifies the existence, in the period from 2001 to 2019, of a public policy with tendencies towards greater regulatory flexibility on the part of the Ministry of Education (MEC). The research highlights a progressive expansion of the offer of distance learning hours in face-to-face undergraduate courses, especially by private HEI, however, the institutional documents of the HEI surveyed demonstrate a policy of transferring responsibility from educational managers, leaving the decisions for faculty initiative. Thus, it is concluded that the policy of implementing distance learning hours in on-site undergraduate courses at UFMS and UFG is limited to the discourse of innovation (need to insert digital culture practices into their educational processes, with a view to a innovative teaching proposal), not going beyond a pseudo-institutionalization marked by repeated practices of lack of responsibility and the lack of definition of clear attributions between MEC, IES, course committee and teachers, resulting, in practice, in the non-institutionalization of the workload offered to distance in face-to-face undergraduate courses at the HEI researched.